A Numerical Strategy to Assess the Stability of Curved Masonry Structures Using a Simple Nonlinear Truss Model - Natalia Pingaro; Martina Buzzetti; Alessandro Gandolfi (Buildings, 2025)
A straightforward and versatile numerical approach is proposed for the nonlinear analysis of single and double-curvature masonry structures. The method is designed to broaden accessibility to both experienced and less specialized users. Masonry units are discretized with elastic quadrilateral elements, while mortar joints are modeled with a combination of elastic orthotropic plate elements or shear panels and elastic perfectly brittle trusses (cutoff bars). This method employs the simplest inelastic finite element available in any commercial software to lump nonlinearities exclusively within the mortar joints. It effectively captures the failure of curved structures under Mode 1 deformation, reproducing the typical collapse mechanism of unreinforced arches and vaults via flexural plastic hinges. The proposed method is benchmarked through three case studies drawn from the literature, each supported by experimental data and numerical results of varying complexity. A comprehensive evaluation of the global force–displacement curves, along with the analysis of the thrust line and the evolution of nonlinearities within the model, demonstrates the effectiveness, reliability, and simplicity of the approach proposed. By bridging the gap between advanced simulation and practical application, the approach provides a robust tool suitable for a wide range of users. This study contributes to a deeper understanding of the behavior of unreinforced curved masonry structures and lays a base for future advancements in the analysis and conservation of historical heritage.